The Effects Of Noise On Biochemical Parameters Using Rat`s Hearts - Muayad S. Rahma; Ni Ni Win; H. M, Rafidah; Razali, Ailin (EuroJournals Publishing, Inc., 2024)
European Journal of Scientific Research, 56 (1). pp. 93-96. ISSN 1450-216X